Recent foraminifera in glaciomarine sediments from three arctic fjords of Novaja Zemlja and Svalbard. - Korsun, S A; Pogodina, I A; Forman, Steven L; Lubinski, David J (PANGAEA, 1995)
Foraminifera were examined in recent (<100 years) fine-grained glaciomarine muds from surface sediments and cores from Nordensheld Bay, Novaja Zemlja, and Hornsund and Bellsund, Spitsbergen. This study presents the first data on modern foraminifera distribution for fjord environments in Novaja Zemlja, Russia. The data are interpreted with reference to the distribution of foraminiferal near Svalbard and the Barents Sea. In Nordensheld Bay, live and dead Nonionellina labradorica and Islandiella norcrossi are most abundant in the outer fjord. Cassidulina reniforme and Allogromiina spp. dominate in the middle and inner fjord. The dominant species are dissimilar to species occurring in other areas of the Barents Sea region, with the exception of Svalbard fjords. The number of live foraminifera (24 to 122 tests/10 cm1) in outer and middle Nordensheld Bay corresponds with values known from the open Barents Sea. However, the biomass (0.03 mg/10 cm**3) is two orders of magnitude less due to smaller foraminiferal test size, which in glaciomarine sediments reflects the absence of larger species, paucity of large specimens, and high occurrence of juvenile foraminifera. The smaller size indicates an opportunistic response to environmental stress due to glacier proximity. The presence of Quinqueloculina stalkeri is diagnostic of glaciomarine environments in fjords of Novaja Zemlja and Svalbard.
Distribution of Recent benthic foraminifera in Arctic galciomarine sediments